2008
DOI: 10.1099/jmm.0.47483-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiling of Mycobacterium tuberculosis in Tunisia: predominance and evidence for the establishment of a few genotypes

Abstract: Typing analyses of 378 Mycobacterium tuberculosis isolates collected between the years 2001 and 2005 from three northern representative regions of Tunisia revealed a highly homogeneous population. Indeed, 84.9 % of all tuberculosis (TB) cases were attributed to the Haarlem, LAM or T families. Strikingly, within each family, more than 60 % of TB cases were due to a single genotype. ST50 (Haarlem3) and ST42 (LAM9) genotypes were exceptionally predominant, representing 46.3 % of all typed isolates. ST50 showed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
1
19
1
1
Order By: Relevance
“…The Manu lineage was initially described as a new family from India in 2004 (16), and later, similar strains in small numbers were reported in a study from Madagascar (8), Soon afterwards, it was tentatively subdivided into the Manu1 (deletion of spacer 34), Manu2 (deletion of spacers 33 and 34), and Manu3 (deletion of spacers 34 to 36) sublineages; and it was suggested that this lineage could represent an ancestral clone of principal genetic group 1 strains (4). More recently, Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (15).…”
Section: Resultsmentioning
confidence: 99%
“…The Manu lineage was initially described as a new family from India in 2004 (16), and later, similar strains in small numbers were reported in a study from Madagascar (8), Soon afterwards, it was tentatively subdivided into the Manu1 (deletion of spacer 34), Manu2 (deletion of spacers 33 and 34), and Manu3 (deletion of spacers 34 to 36) sublineages; and it was suggested that this lineage could represent an ancestral clone of principal genetic group 1 strains (4). More recently, Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (15).…”
Section: Resultsmentioning
confidence: 99%
“…The factors that might contribute to the adaptability of M. tuberculosis strains or lineages to a particular population or zone are poorly understood. As hypothesized for the Tunisian family [15], mass BCG vaccination strictly applied for decades might have profoundly shaped the population structure of M. tuberculosis by concurrently favoring the selection and accommodation of particular genotypes, as the LAM10_ CAM family in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Soon afterwards, it was tentatively subdivided into the Manu1 (deletion of spacer 34), Manu2 (deletion of spacers 33 and 34), and Manu3 (deletion of spacers 34 to 36) sublineages, and it was suggested that it could represent an ancestral clone of principal genetic group (PGG) 1 strains (4). Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (17) and more recently in a study from Egypt, where it represented as much as 27% of all isolates (15). However, according to a recent report, a fraction of Manu2 patterns could also arise due to mixed infection by a strain belonging to evolutionarily recent H, LAM, X, and T lineages with a Beijing strain, a risk that may be excluded by looking for genomic deletion of region of difference RD105, which is characteristic of the Beijing lineage (26).…”
Section: Resultsmentioning
confidence: 99%